Reducing the Risk of Severe Complications among Patients with Clostridium difficile Infection - Kamran Manek; Victoria Williams; Sandra Callery; Nick Daneman (Canadian Journal of Gastroenterology)
BACKGROUND: The incidence and severity of Clostridium difficile infections are increasing, and there is a need to optimize the prevention of complicated disease.